Notes on Length-Weight Relationship and Condition Factor of Fresh Water Fish, Labeo boga (Hamilton) (Cypriniformes: Cyprinidae) - Pervin, M Rokshanara; Mortuza, M Golam (University Journal of Zoology, Rajshahi University, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> No Abstract Key words: Labeo boga, length-weight relationship, condition factor doi:10.3329/ujzru.v27i0.1964 Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 97-98